Chronotope between theory and application A study of the dialectic of love and war with Rashad Abu Shawer and Ernest Hemingway - Hussain, Kinan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The relationship between man and both love and war is deeply rootedthroughout history, two powers which affect one another, although each one has its own language, and own weapons. And since literature is the mirror of society movement, so it reflects war as an instinctive phenomenon inherent in human, and associated with feelings of love which affects and affected by, showing manifestations of love and war in its variant literary genres. Hence becomes the choice of the topic, attempting to monitor the nature of love, in a particular temporal condition, which is the time of war, and tracing its impact on war in the spatial space. And according to the nature of the characters which destinies are determined by an external compressing reality, compared to some other characters with an internal force almost like a torque force stands to face that reality, either succeeded or failed in their goal. And what I want to shed the light on in my research is not related to the act of writing about love in the time of war, rather than the novelist works which approaches love in the time of war by Rashad Abu Shawer,Ernest Hemingway observed throughout the exposure of the elements of time and space.